The O.J. Simpson Verdict: A Lesson in Black and White - Lassiter, Christo (1996)
This article is an attempt to analyze the O.J. Simpson verdict and the press coverage of it, to suggest ways not only of improving criminal justice in a diverse community, but also of improving press coverage of criminal justice in a diverse community. Part Two of this essay is subdivided into two sections. The first section surveys the op-ed pages of major newspapers to evaluate the analysis of, and the commentary on, the O.J. Simpson verdict. The second section deconstructs the press' spin on the verdict. Part Three of this article discusses the role of a jury and proof beyond a reasonable doubt among a diverse set of jurors. Part Four is an effort to explain reasonable doubt and to provide the factual analysis in support of the jury's verdict in the O.J. Simpson case-an exercise which the press largely shrugged off. The conclusion contains no easy answer, but suggests a role for concerned public constituencies in demanding a better brand of criminal justice and press coverage of criminal justice